Dampak Intesitas Mengakses Media Sosial Dengan Body Image Pada Remaja - Sari, Novia Aspita; Rahayu Z, Sri Putri (Batanang : Jurnal Psikologi, 2022)
Adolescence is a transition period from childhood to adulthood. During this period, teenagers face many developmental challenges, both from within and outside themselves, especially in the social area. One of the tasks that must be achieved by teenagers is to accept and utilize the physical conditions of teenagers to overcome developmental challenges. Every individual has an ideal image of what they want, including the ideal body shape they want to have, this is related to body image. The gap between the shape that an individual perceives and the shape that is considered ideal will lead to dissatisfaction with their body. The intensity of accessing social media is one of the social factors that has a strong relationship to teenagers' body image. Here the basic theoretical content is taken from various sources that have been read so that it can help expand knowledge about the impact of the intensity of accessing social media on body image in adolescents.Keywords : social media, body image, adolescence